2002
DOI: 10.1101/gr.221202
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of the Human Proteome

Abstract: This paper reports an analysis of the encoded proteins (the proteome) of the genomes of human, fly, worm, yeast, and representatives of bacteria and archaea in terms of the three-dimensional structures of their globular domains together with a general sequence-based study. We show that 39% of the human proteome can be assigned to known structures. We estimate that for 77% of the proteome, there is some functional annotation, but only 26% of the proteome can be assigned to standard sequence motifs that characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 49 publications
3
53
0
1
Order By: Relevance
“…This phenomenon is consistent with the idea that relatively young folds may not have had enough time to procreate families, thus obscuring trends between these attributes. Early structural characterization of the human proteome indicated significant differences in SCOP superfamily composition between disease and non-disease proteins [24]. In this and a previous work [7], it was found that disease proteins tend to have folds with fewer families than non-disease proteins (see Protocol S2).…”
Section: Discussionmentioning
confidence: 55%
“…This phenomenon is consistent with the idea that relatively young folds may not have had enough time to procreate families, thus obscuring trends between these attributes. Early structural characterization of the human proteome indicated significant differences in SCOP superfamily composition between disease and non-disease proteins [24]. In this and a previous work [7], it was found that disease proteins tend to have folds with fewer families than non-disease proteins (see Protocol S2).…”
Section: Discussionmentioning
confidence: 55%
“…27 Unsurprisingly, there are numerous examples of variant TMEM proteins in human genetic disorders, [28][29][30][31][32][33][34] and in that context, we do gain pathomechanistic clues about the disorder. We have reported enrichment of TMEM domains in the ciliary proteome, 35 raising the possibility that the present constellation of phenotypes could be part of the ciliopathy spectrum.…”
Section: Renal Defectsmentioning
confidence: 99%
“…Similar attempts have been made in the past by Muller et al (38). They have used PSI-BLAST for much of their analysis, apart from IMPALA, to assign structural/functional domains.…”
Section: Introductionmentioning
confidence: 88%